Advancing Knowledge of the Bio-Cultural Complexities of Low Energy Availability: The Value of Mixed-Methods Approaches - Katherine L. Schofield; Holly Thorpe; Stacy T. Sims (Physiologia, 2023)
Low energy availability (LEA) is a complex health condition that most commonly affects female athletes. Research on LEA is weighted to quantitative approaches, and few studies have employed qualitative methods to understand the development of LEA. Current research fails to understand the complexity of LEA by largely operating within isolated research paradigms. This paper aims to demonstrate the value of integrating a mixed-methods research approach to understand the influence of sporting cultures on the physiological experiences of female athletes with LEA. The mixed-methods approach implemented the use of physiological (quantitative) and socio-psychological (qualitative) data obtained from elite female athletes in three sports: triathlons and running, (n = 11), rugby sevens (n = 9), and track cycling (n = 10). The physiological data consisted of energy availability, haematological analysis, bone health, and body composition. The socio-psychological data consisted of individual semi-structured interviews with topics covering nutrition, body image, the impact of the sporting environment, and experience with LEA. The interview data were thematically analysed. By bringing qualitative and quantitative data together, this paper illustrates the complex relationship between sporting culture and the physiology of LEA. First, endurance athletes categorised as having an LEA showed a positive correlation between the relative energy intake (EI) and serum ferritin, with the interviews revealing a focus on a low body weight and reducing the EI. Second, the interviews with the rugby players showed a strong but hierarchical team culture, with the experienced players monitoring and controlling the EI of novice players. Third, among the cyclists, the EI was reduced in those categorised as having an LEA, with the interviews revealing a coach–athlete power relationship impacting dietary behaviours. To conclude, this paper demonstrates how mixed methods are important for capturing how different sporting cultures impact athletes’ socio-psychological and physiological experiences of LEA.